Insight on trans-plasma membrane behavior of virus-infected plant cells - Luvisi, A.; Rinaldelli, E. (Advances in Horticultural Science, 2017)
Little is known about the ion fluxes generated during plant-virus interactions, despite significant losses caused by viruses to agricultural crops. Changes in average ion currents were identifying an early event in the signal transduction pathway related to virus/host interaction. While significant decrease in the average inward currents, mainly due to Ca2+ moving into the cell was observed, the role of potassium may be significant. Host specific K+ efflux with a concomitant decrease in the intracellular K+ was observed in tobacco plants during the early minutes after infection, suggesting many hypothesis about the role of potassium in host-virus interaction. In the last years, trans-plasma membrane potential was evaluated for some viruses, observing as effect on membrane was different in relation to virus infection and host. Conversely, settle virus infection generally lead to an increase of activity in trans-plasma membrane electron transport.